How to Teach Sex Education? - Hidayatussyifa, Hidayatussyifa; Rachmayanie Jamain, Ririanti (Journal of English Language and Education, 2025)
A proper understanding of sex education, which is in accordance with the stage of sexual development of adolescents, is very important to prevent problems related to their sexual development. The purpose of this study was to analyze the effectiveness of cinematherapy techniques in group guidance services on the understanding of sex education of class VIII students at SMP Negeri 2 Banjarmasin. This research method applies a quantitative approach with an experimental type of one group pre-test post-test design. The sample was selected 5 students of class VIII of SMP Negeri 2 Banjarmasin using purposive sampling technique. Data collection instruments include observation, interviews and documentation, data analysis is done with descriptive statistics and Paired Sample T Test. The results of the analysis showed a significance value of 0.000 (significant value 0.05), indicating that Ha, namely group guidance services with cinematherapy techniques are effective for improving the understanding of sex education of 8th grade students at SMP Negeri 2 Banjarmasin. Cinematherapy technique is one of the technology-based counseling techniques that offers convenience for students to access information about sex education, so it is no longer taboo to know about it.